The Effectiveness of the Probalusan Model on Improving Knowledge and Process Skills in Science Learning for Junior High Schools in Jayapura City - Rosaniya E. Rehiara (Postgraduate, University of Mataram, 2025)
This study aims to determine the effectiveness of the Probalusan model in improving science process knowledge and skills in science learning at SMP Negeri 3 Jayapura City. This study used a quasi-experimental Nonequivalent Control Group design with a purposive sampling technique, where the schools studied were SMP Negeri 1 and SMP Negeri 3 Jayapura City. Data collection techniques included tests and observation sheets. Data analysis was carried out descriptively qualitatively, using independent sample-test, MANOVA test, N-Gain, and effect-size test. The results of the study showed that: the Probalusan model can improve science process knowledge and skills in science learning at SMP Negeri 3 Jayapura City. The results of the difference test showed a significant difference between the scores of students taught using the Probalusan Science learning model and the scores of students taught using the conventional model. The scores of science process knowledge and skills of students taught using the Probalusan Science model were higher than the scores of participants taught using the conventional model. The effectiveness of the Probalusan Science learning model is categorized as high based on the N-Gain and effect-size values.